Mompreneurs: A Study of The Entrepreneurial Behavior of Women Traditional Cake Business In Rumpia Village, Majauleng District, Wajo District - Yuliana Yuliana (The Eastasouth Management and Business, 2023)
This study aims to identify the entrepreneurial behavior of mothers in the traditional cake-making industry in the Village of Rumpia Majuleng District, Wajo Regency. The research method used is descriptive research with a qualitative approach. Samples and populations taken are traditional pastry entrepreneurial mothers in the village of Rumpia. As for the data collection techniques by interview, observation, and documentation. The result of the research is the traditional cake of notice is not desperate with what it gets and tries to believe the buyer so they don't lose customers they have a very high power of maintaining its efforts and they don't pose asa in the face of problems in their efforts